High glucose promotes the migration of retinal pigment epithelial cells through increased oxidative stress and PEDF expression - Farnoodian, Mitra (Am J Physiol Cell Physiol, 2016)
Defects in the outer blood-retinal barrier have significant impact on the pathogenesis of diabetic retinopathy and macular edema. However, the detailed mechanisms involved remain largely unknown. This is, in part, attributed to the lack of suitable animal and cell culture models, including those of mouse origin. We recently reported a method for the culture of retinal pigment epithelial (RPE) cells from wild-type and transgenic mice. The RPE cells are responsible for maintaining the integrity of the outer blood-retinal barrier whose dysfunction during diabetes has a significant impact on vision. Here we determined the impact of high glucose on the function of RPE cells. We showed that high glucose conditions resulted in enhanced migration and increased the level of oxidative stress in RPE cells, but minimally impacted their rate of proliferation and apoptosis. High glucose also minimally affected the cell-matrix and cell-cell interactions of RPE cells. However, the expression of integrins and extracellular matrix proteins including pigment epithelium-derived factor (PEDF) were altered under high glucose conditions. Incubation of RPE cells with the antioxidant N-acetylcysteine under high glucose conditions restored normal migration and PEDF expression. These cells also exhibited increased nuclear localization of the antioxidant transcription factor Nrf2 and ZO-1, reduced levels of β-catenin and phagocytic activity, and minimal effect on production of vascular endothelial growth factor, inflammatory cytokines, and Akt, MAPK, and Src signaling pathways. Thus high glucose conditions promote RPE cell migration through increased oxidative stress and expression of PEDF without a significant effect on the rate of proliferation and apoptosis.